2018–2019 Florida Citrus Production Guide: Greasy Spot - Megan M. Dewdney (EDIS)
Greasy spot is caused by the fungus Mycosphaerella citri, which has been recently renamed Zasmidium citri-griseum. Management must be considered in groves intended for processing and fresh market fruit. Greasy spot is usually more severe on leaves of grapefruit, pineapples, Hamlins, and tangelos than on Valencias, Temples, Murcotts, or most tangerines and their hybrids. Greasy spot rind blotch (GSRB) is particularly problematic for grapefruit destined for the fresh fruit market. This 3-page fact sheet is part of the 2018–2019 Florida Citrus Production Guide. Written by Megan M. Dewdney and published by the Plant Pathology Department, May 2018.